The founder of cardiovascular surgery in Siberia – academician of RAMS Ye.N. Meshalkin - G. V. Fyodorova; D. V. Scherbakov (Бюллетень сибирской медицины, 2005)
The article is devoted to the historiographic biography of the academician of RAMS Ye.N.Meshalkin, the founder of cardiovascular surgery in Siberia. Biographic information of Ye.N. Meshalkin and his scientific papers are presented. The history of creation of the first-rate cardiosurgical center over Ural that was named after the scientist was presented. The emphasis was placed on the scientific school created and directed by Ye.N. Meshalkin for a long time.